2017
DOI: 10.23953/cloud.ijaast.229
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore Producing Aspergillus spp as Bioinoculant for Enhanced Growth of Mung Bean

Abstract: Two fungal species A. niger and A. parasiticus isolated from agriculture field were used in the present study. These two fungal isolates were studied for the siderophore production on the modified CAS agar medium. On daily observation it was observed that the growth was increased along with the production indicating the change in colour of CAS dye from blue to purplish red by A. niger and Yellow by A. parasiticus. Quantitative determination of siderophore production was further studied using liquid medium. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…In the same test for the siderophore of Aspergillus niger MH603592, its show maximum absorbance at 450 which is confirmed the hydroxymate nature of siderophores (Fig. 4-II) and is in accordance with the report of (Patel et al, 2017), Moreover, (Neilands, 1981) have observed that the iron hydroxamate complex is more stable and therefore more significant in the rhizosphere. While no evidence for carboxylate in the spectrophotometric test for the both isolates.…”
Section: Resultssupporting
confidence: 87%
“…In the same test for the siderophore of Aspergillus niger MH603592, its show maximum absorbance at 450 which is confirmed the hydroxymate nature of siderophores (Fig. 4-II) and is in accordance with the report of (Patel et al, 2017), Moreover, (Neilands, 1981) have observed that the iron hydroxamate complex is more stable and therefore more significant in the rhizosphere. While no evidence for carboxylate in the spectrophotometric test for the both isolates.…”
Section: Resultssupporting
confidence: 87%
“…Aspergillus spp. is known to produce hydroxamate-like siderophores (Haas 2014;Patel et al 2017). During this study, siderophore production was noted in eight Aspergillus isolates followed by the isolates of Curvularia, Alternaria, Monotospora, Penicillium, Trichoderma, Chlamydospora, Mucor, and Trichothecium.…”
Section: Discussionmentioning
confidence: 69%
“… Ritika and Utpal (2014) showed in their review that the use of Azotobacter as an N-biofertilizer increased the growth and yield of various crops under field conditions with a percentage increase of up to 40% for Cauliflower and 15–20% for Maize compared to conventional fertilizers. These beneficial effects can be attributed to the biosynthesis of biologically active substances, the stimulation of rhizospheric microorganisms, the production of phytopathogen inhibitors, and improved nutrient availability of N, P, carbon, and sulfur, through BNF and mineralization of organic residues in soil ( Lenart, 2012 ; Patel et al, 2017 ). Numerous studies described crop responses to Azotobacter inoculation under greenhouse and field conditions.…”
Section: Discussionmentioning
confidence: 99%